Virtual, augmented, and mixed reality in the University environment: an analysis of scientific production. - Colomo-Magaña, Ernesto; Cívico-Ariza, Andrea; Ruiz-Palmero, Julio; Guillén-Gámez, Francisco David (Springer Nature, 2025)
Augmented, virtual, and mixed reality offer digital alternatives for implementing innovative educational processes, significantly expanding opportunities in university education due to the available resources and the psycho-evolutionary development of students. This study aimed to analyze the scientific production on this topic in Scopus using bibliometric techniques. Following the PRISMA statement, the final sample comprised 1,257 articles published between 2014 and 2023, utilizing various bibliometric analyses. The results indicate a surge in production over the last five years, with most articles indexed in the areas of social sciences, engineering, and medicine, aligning with the subject matter of the journals with the highest number of publications. While the United States and China are the most prolific countries, the leading authors and institutions are predominantly from Spain. In addition to meta-analyses and systematic reviews, the most cited articles focus on the use of augmented and virtual reality in health sciences within universities. Makransky and Akçayir (bibliographic coupling) are highlighted as the most influential authors, along with the duo Cabero and Barroso in the field of educational sciences (co-citation). Emerging research areas (co-occurrence) are oriented towards factors affecting learning processes with these digital resources, such as motivation and anxiety management. In conclusion, further research is needed to explore the potential of these resources for university training due to their positive effects on learning.
Keywords: Tecnología educativa; Investigación; Universidades; Realidad virtual; Augmented reality; Virtual reality; Mixed reality; University; Scientific production